2024
DOI: 10.12912/27197050/179421
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antioxidant and Anti-Inflammatory Capacities of Different Extracts from <i>Cistus ladanifer</i> L. Leaves in the Ait Ammart Region (Northern Morocco)

Omar Benamari,
Amina Labhar,
Naoufal Ahidar
et al.

Abstract: Plants are a significant source for identifying new compounds (particularly secondary metabolites) with medicinal value for drug development, pharmaceuticals, and food additives. Many of these healing plants are frequently used in conventional medicine to treat and prevent various diseases. The purpose of the current research is to assess the total phenolic content (TPC) and total flavonoid content (TFC) for phytochemical analysis, DPPH and FRAP (Ferric Reducing Antioxidant Power) assays for antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These results explain the importance of solvent polarity in extracting antioxidant compounds from the sample. Indeed, higher-polarity solvents (ethanol and ethyl acetate) extracted more hydrophilic antioxidant compounds, such as flavonoids and polyphenols, due to the presence of hydroxy groups that contribute to antioxidant activity [26,27]. Less-polar solvents, such as hexane, have a stronger affinity for lipophilic compounds, which may include both non-antioxidant and antioxidant compounds [26].…”
Section: Evaluation Of Antioxidant Activity (Ac)mentioning
confidence: 99%
“…These results explain the importance of solvent polarity in extracting antioxidant compounds from the sample. Indeed, higher-polarity solvents (ethanol and ethyl acetate) extracted more hydrophilic antioxidant compounds, such as flavonoids and polyphenols, due to the presence of hydroxy groups that contribute to antioxidant activity [26,27]. Less-polar solvents, such as hexane, have a stronger affinity for lipophilic compounds, which may include both non-antioxidant and antioxidant compounds [26].…”
Section: Evaluation Of Antioxidant Activity (Ac)mentioning
confidence: 99%
“…Moreover, this plant possesses inherent antioxidant properties due to phenolic compounds and their ability to scavenge free radicals, such as syringic acid and sinapinic acid, which contributes to the antioxidant and anti-inflammatory activity [175] , [18] , [196] , [2] , [3] , [95] . The antimicrobial efficacy of cannabis’s essential oil was tested against Candida and diverse pathogenic bacterial species, the study reported that it had moderate antimicrobial efficiency and exhibited interesting antioxidant potency [133] .…”
Section: Therapeutic Proprieties Of Cannabismentioning
confidence: 99%
“…Since antiquity, humans have used plants in traditional medicine for several benefits to treat various diseases [1][2][3]. The scientific and technological evolution has approved the importance of aromatic and medicinal plants (AMP), a significant source for developing and synthesizing drugs or pharmacologically active compounds [4].…”
Section: Introductionmentioning
confidence: 99%